Factors affecting the use of neurally adjusted ventilatory assist in the adult critical care unit: a clinician survey. Issue 1 (8th December 2020) - Hadfield, Daniel; Rose, Louise; Reid, Fiona; Cornelius, Victoria; Hart, Nicholas; Finney, Clare; Penhaligon, Bethany; Harris, Clare; Saha, Sian; Noble, Harriet; Smith, John; Hopkins, Philip Anthony; et al.
Abstract : Background: Neurally adjusted ventilatory assist (NAVA) involves an intricate interaction between patient, clinician and technology. To improve our understanding of this complex intervention and to inform future trials, this survey aimed to examine clinician attitudes, beliefs and barriers to NAVA use in critically ill adults within an institution with significant NAVA experience. Methods: A survey of nurses, doctors and physiotherapists in four Intensive Care Units (ICUs) of one UK university-affiliated hospital (75 NAVA equipped beds). The survey consisted of 39 mixed open and structured questions. The hospital had 8 years of NAVA experience prior to the survey. Results: Of 466 distributed questionnaires, 301 (64.6%) were returned from 236 nurses (78.4%), 53 doctors (17.6%) and 12 physiotherapists (4.0%). Overall, 207/294 (70.4%) reported clinical experience. Most agreed that NAVA was safe (136/177, 76.8%) and clinically effective (99/176, 56.3%) and most perceived 'improved synchrony', 'improved comfort' and 'monitoring the diaphragm' to be key advantages of NAVA. 'Technical issues' (129/189, 68.3%) and 'NAVA signal problems' (94/180, 52.2%) were the most cited clinical disadvantage and cause of mode cross-over to Pressure Support Ventilation (PSV), respectively. Most perceived NAVA to be more difficult to use than PSV (105/174, 60.3%), although results were mixed when compared across different tasks. More participants preferred PSV to NAVA for initiating ventilator weaning (93/171 (54.4%) vs 29/171 (17.0%)). A key barrier to use and a consistent theme throughout was 'low confidence' in relation to NAVA use. Conclusions: In addition to broad clinician support for NAVA, this survey describes technical concerns, low confidence and a perception of difficulty above that associated with PSV. In this context, high-quality training and usage algorithms are critically important to the design and of future trials, to clinician acceptance and to the clinical implementation and future success of NAVA.